Uncertainty management during the emergence and evolution of global ecosystems - Santos, Matheus Graciani dos (2023)
Leading firms in a global context have engaged with external actors located outside their home country, creating local and global ecosystems to materialize their innovative focal value propositions. Because knowledge is dispersed between people, places, and time, these focal firms must access internationally dispersed external actors and create the proper alignment between them for their innovations to fully deliver value to their global customers. To better understand this process, we conducted two phases of indepth qualitative research. Phase one was a multicase qualitative study of four focal firms leading global ecosystems to answer how these organizations use global ecosystems to manage local and global uncertainties. Phase two builds on this initial research, using a sample of seven focal firms leading global ecosystems to answer how they lead the processes of global ecosystem emergence and evolution under conditions of local and global uncertainty. We used qualitative data, composed of interviews with innovation managers, ecosystem managers, open innovation managers, investors, public employees, and entrepreneurs, as well as documents, reports, press releases, and articles in the business press. We focused on focal firms with operations in Brazil, either headquartered or with subsidiaries in this country. What resulted from these eorts are two complementary theoretical frameworks on uncertainty management in global ecosystems and global ecosystem emergence and evolution. Phase one of our research reveals that focal firms combine uncertainty scope assessment with uncertainty management governance and uncertainty management strategies to successfully mitigate local and global uncertainties. Phase two of our research shows that focal firms face the challenges of defining a local and global ecosystem value proposition and dealing with structure uncertainty during global ecosystem emergence. During global ecosystem evolution, these focal firms must define and implement local and global ecosystem governance and orchestrate their local and global ecosystems. We hope that this research will draw interest to the understudied subject of global ecosystems and convince academics and practitioners alike that global ecosystems matter.